Towards 6G Network Slicing - Moreira, Rodrigo; Silva, Flávio de Oliveira (Anais do Workshop de Redes 6G (W6G), 2021)
Networks should connect communicating peers, supporting vertical services requirements. The network evolution towards 6G requires native network slicing techniques. Some literature approaches claim network slice realization, but they do not convincingly address the deployment across multiple Autonomous Systems. This work investigates the current 6G network slicing landscape, presents some gaps, and introduces the concept of the recursive network slicing between multiple Autonomous Systems, supported by the NASOR approach. This innovative concept supports implementing new network services required by the 6G vision. This work also sheds light on the 6G requirements for network slicing.